4G LTE Network Performance for XL Axiata provider in Lolong Belanti Area - Abdi Abdullah; Dikky Chandra; Zurnawita Zurnawita; Dinda Kurnia Illahi (Politeknik Negeri Padang, 2025)
This measurement aims to analyze the quality of the 4G LTE network and its relationship with the quality of service (QoS) parameters on the performance of TCP/IP provider XL Axiata in Lolong Belanti Village. The measurement results show that the network with the quality category